2020
DOI: 10.1101/2020.09.01.271650
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synchrony in the periphery: inter-subject correlation of physiological responses during live music concerts

Abstract: A concert is a common event at which people gather to share a musical experience. While techniques are increasingly offering insights into naturalistic stimuli perception, this study extended methods to a more ecological context in order to explore real-world music listening within a concert setting. Cardiorespiratory, skin conductance, and facial muscle responses were measured from participants attending one of three concerts with live chamber music performances of works of varying Western Classical styles (V… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 113 publications
(155 reference statements)
2
18
0
Order By: Relevance
“…We do not suggest that listener engagement ceases or decreases at the musical climax, but rather that the specific nature of engagement at this point is not evident or indexed by ISC. Recent work by Chabin et al (2020) has used EEG oscillatory band power to identify neural correlates of chills and emotional pleasure during natural music listening, while Czepiel et al (2020) linked ISC of physiological responses to live music to musical elements such as structural segmentation boundaries. Thus, future work could consider using EEG-ISC alongside complementary analysis approaches and response modalities to more fully characterize listener experiences of music.…”
Section: Discussionmentioning
confidence: 99%
“…We do not suggest that listener engagement ceases or decreases at the musical climax, but rather that the specific nature of engagement at this point is not evident or indexed by ISC. Recent work by Chabin et al (2020) has used EEG oscillatory band power to identify neural correlates of chills and emotional pleasure during natural music listening, while Czepiel et al (2020) linked ISC of physiological responses to live music to musical elements such as structural segmentation boundaries. Thus, future work could consider using EEG-ISC alongside complementary analysis approaches and response modalities to more fully characterize listener experiences of music.…”
Section: Discussionmentioning
confidence: 99%
“…Ratings of excitement were associated with similar respiratory phases indicating a synchronization effect. In using synchrony as a measure of reliable stimulus-evoked physiological responses, synchronized respiration and skin conductance responses were more probable during faster music, and occurred during phrase repetitions, transitions and structural boundaries in a concert setting (Czepiel et al, 2020). Interbrain coherence, that is, neural synchronization , was found between a violinist and listeners using near-infrared spectroscopy in a laboratory setting (Hou et al, 2020).…”
mentioning
confidence: 99%
“…This proneness to become a hit could potentially be estimated by neural similarity measures. As several studies have already indicated that neural synchronization increased with specific aspects of music, such as rhythm, melody, tempo, and phrase repetitions ( Czepiel et al, 2020 ; Kaneshiro et al, 2020 ), it is agreed that neural similarity identifies emotions at the level of musical features and we hypothesize it will therefore serve as a strong predictor of mega-hit potential.…”
Section: Discussionmentioning
confidence: 69%
“…The subjective experience of music was found to relate to neural synchrony in the affective processing circuit ( Sachs et al, 2020 ), and Kaneshiro et al (2020) showed that basic musical features, such as rhythm and melody, elicited significantly higher neural correlation compared to scrambled musical samples. Additionally, Czepiel et al (2020) calculated the ISC during three live concerts and showed that tempo was consistently related to increased neural synchrony as well as phrase repetitions, transitional passages, and boundaries.…”
Section: Introductionmentioning
confidence: 99%